2020
DOI: 10.3389/fmats.2020.577299
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Behavior of Reinforced Concrete Beams Reinforced with Glass Fiber Reinforced Polymer Rectangular Tubes

Abstract: Glass fiber reinforced polymer (GFRP) pultruded rectangular tubes were used externally to confine Reinforced Concrete (RC) beams in this experimental study, aiming to improve the corrosion resistance of the RC beams in the harsh environment (e.g., Hydraulic structures and Marine structures). The flexural behavior of the composite beams reinforced with GFRP tubes was investigated by using four-point bending test. The experimental program involved the testing of six beam specimens reinforced with or without the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Anas et al [ 23 ] investigated the structural performance of square slab specimens reinforced with different types of FRPs, and they found that samples with CFRP bars exhibited exceptional impact resistance. Using a four-point bending test, Yuan et al [ 24 ] examined the flexural behavior of reinforced concrete (RC) beams strengthened with GFRP tubes. The results demonstrated that the strengthening solution improved the composite element’s flexural strength and bending stiffness under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Anas et al [ 23 ] investigated the structural performance of square slab specimens reinforced with different types of FRPs, and they found that samples with CFRP bars exhibited exceptional impact resistance. Using a four-point bending test, Yuan et al [ 24 ] examined the flexural behavior of reinforced concrete (RC) beams strengthened with GFRP tubes. The results demonstrated that the strengthening solution improved the composite element’s flexural strength and bending stiffness under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…However, challenges such as low resistance to transverse loads and susceptibility to environmental factors Rashid et al, 2020) hinder FRP usage. Understanding these mechanisms is essential to mitigate environmental effects and ensure the longterm performance of structures using FRP materials (Yuan et al, 2020).…”
Section: Reinforcement Materialsmentioning
confidence: 99%